The Link between Economic Growth, Electricity Consumption, and CO2 Emissions: Evidence from Indonesia - Taufiq Marwa; Abdul Bashir; Dirta Pratama Atiyatna; Ichsan Hamidi; Mukhlis Mukhlis; Sukanto Sukanto (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2022)
This study investigates the relationship between economic growth, electricity consumption, and CO2 emissions in Indonesia. The data utilized time series for 1971-2020 obtained from the WDI database 2021. The method utilized the ADRL and VEC models. The findings indicate that in the long run, economic growth and electricity consumption positively affect CO2 emissions. The short-run effect that occurs from economic growth is significant and negative, while the lag of CO2 emission is positive on CO2 emissions. There is a two-way causality between economic growth and electricity consumption in the short run. There is a unidirectional causality flowing from CO2 emissions to economic growth. A significant ECT coefficient has confirmed that the long-run relationship between variables in the model used is valid. The policies offered are applying emission taxes, encouraging energy conservation to control emissions, and encouraging efficient and sustainable electricity supply.How to Cite:Marwa, T., Bashir, A., Atiyantna, D.P., Hamidi, I., Mukhlis, M., Soekanto, S. (2022). The Link between Economic Growth, Electricity Consumption, and CO2 Emissions: Evidence from Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 11(2), 253-272. https://doi.org/10.15408/sjie.v11i2.26286.